Preferred mode of delivery and its associated factors in pregnant women with a previous cesarean scar at a tertiary care hospital in Ethiopia: institutional-based cross-sectional study - Abebe Chanie Wagaw; Ashenafi Kibret Sendekie; Solomon Gedlu Nigatu; Getasew Sisay Mihretie (BMC, 2023)
Abstract Background Vaginal births after cesarean or elective repeat cesarean sections (CS) are the options for delivery after one cesarean scar. However, there is a lack of data regarding the preferred next mode of delivery in Ethiopia after a previous cesarean section. Thus, this study assessed the preferred mode of delivery and determinants after one previous CS in the antenatal clinic at the University of Gondar Comprehensive Specialized Hospital (UoGCSH). Methods An institutional-based cross-sectional study was conducted among pregnant mothers with one previous CS at UoGCSH from March to August 2022. Structured questionnaires were used to collect the data. The collected data were entered, cleaned, and edited using Epi-data 4.6 and exported to SPSS version 26 for analysis. A binary logistic regression was performed to assess the determinants of the preferred mode of delivery. A p-value of < 0.05 at the 95% confidence level (CI) was considered statistically significant. Results The majority, 71.5% (95% CI: 64.7, 77.1), of participants preferred the trial of labor after cesarean (TOLAC) as their mode of delivery. Mothers who were married (AOR = 4.47, 95% CI: 1.19-16.85), had a diploma educational level (AOR = 3.77, 95% CI: 1.84-12.36), had previous post-cesarean complications (AOR = 3.25, 95% CI: 1.08-9.74), and knew about the success of the trial of labor after cesarean (AOR = 13.56, 95% CI: 4.52-37.19) were found to prefer the trial of labor compared with their counterparts. Conclusion This study concluded that most pregnant mothers preferred labor trials after one CS, which is a bit lower but comparable with recommended practice guidelines. Providing adequate information and counseling mothers to make informed decisions about their preferred mode of delivery could be substantial.